2015
DOI: 10.1109/tmag.2014.2357452
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Temperature Distribution in the Stator of Large Synchronous Machines Considering Heat Conduction and Heat Convection

Abstract: The aim of this paper is the characterization of the convective heat transfer and its treatment in a 3-D model to calculate the heat transfer and related temperature distribution in large synchronous machines. The wall heat transfer coefficients in the ventilation ducts have been correlated to various design parameters by several computational fluid dynamics simulations and have been defined at the boundaries at the tooth and yoke iron in the numerical model. The losses have been determined in the copper bars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Due to the advancement of the computational power in the recent years, using CFD conjugate thermal analysis for electric machines became a focus of several researchers [107,108]. Previous research using conjugate CFD thermal analysis focused on air cooled systems [109][110][111], water or oil cooled systems [80,112,113] and hybrid systems [114]. In the recent study performed by Schrittwieser et al [111], the authors compared between the simulation results based on a conjugate heat transfer model and those obtained by conventional heat transfer model (no conduction).…”
Section: Cfd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the advancement of the computational power in the recent years, using CFD conjugate thermal analysis for electric machines became a focus of several researchers [107,108]. Previous research using conjugate CFD thermal analysis focused on air cooled systems [109][110][111], water or oil cooled systems [80,112,113] and hybrid systems [114]. In the recent study performed by Schrittwieser et al [111], the authors compared between the simulation results based on a conjugate heat transfer model and those obtained by conventional heat transfer model (no conduction).…”
Section: Cfd Analysismentioning
confidence: 99%
“…Previous research using conjugate CFD thermal analysis focused on air cooled systems [109][110][111], water or oil cooled systems [80,112,113] and hybrid systems [114]. In the recent study performed by Schrittwieser et al [111], the authors compared between the simulation results based on a conjugate heat transfer model and those obtained by conventional heat transfer model (no conduction). The results showed that the temperature deviations between the two models are relatively small and that the conventional heat transfer model are generally applicable for calculating stator temperatures with the benefit of shorter calculation times.…”
Section: Cfd Analysismentioning
confidence: 99%
“…The last unknown parameter is the fluid reference temperature T ref which must be defined to compute the convective heat flux. The energy balance equation, based on the first law of thermodynamics, has to be added to take account of the fluid heating up due to the heat discharged over the walls, presented in Schrittwieser et al (2015). Afterwards the fluid inlet temperature and the mass flow rate are given as input.…”
Section: Validationmentioning
confidence: 99%
“…Gbé gbé et al performed the damper currents simulation of large hydro-generator using the combination of FEM and coupled circuits models [7]. Schrittwieser et al analyzed on temperature distribution in the stator of large synchronous machines considering heat conduction and heat convection [8]. Some other experts extensively studied hydrogenerator [9], [10], but very few focused on the influence of rotor structure on the fluid flow and temperature distribution in the rotor region of hydrogenerator.…”
Section: Introductionmentioning
confidence: 99%